ADVANCED RFID CIRCUIT BREAKER SYSTEM FOR EFFICIENT ACCESS CONTROL - Hathiram, Easlavath; Miryala, Dr. Kiran Jyothi; Akhil, Guguloth (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The safety of line workers has grown significantly along with the advancement of various electronic devices. Although line workers turn off circuit breakers to protect themselves, there is still a chance that someone could unintentionally turn the breaker on while the worker is still on the job. A basic project called the Rfid Based Circuit Breaker uses an Rfid to manage electrical lines. Due to a communication breakdown between the maintenance personnel and the electrical substation, lineman injuries from electrical mishaps are on the rise these days while fixing the electrical lines. In order to guarantee lineman safety, this project provides a solution to the issue. The lineman is located in this section of the electrical cables. This project is set up so that in order to turn on or off the electrical line, maintenance personnel or linemen must swipe the RFID. In the event that an electrical line malfunctions, the line man will now turn off the power supply by pulling the RFID, allow the line to be repaired without difficulty, and then, upon arriving at the substation, turn on the supply to that specific line. Every electrical wire has its own unique RFID.